2020
DOI: 10.1001/jamaneurol.2019.3946
|View full text |Cite|
|
Sign up to set email alerts
|

Perception of Dementia Risk and Preventive Actions Among US Adults Aged 50 to 64 Years

Abstract: IgG compared with MOG-IgG. Together, these sex differences and the greater detection of MOG-IgG, especially in children, suggests that central demyelinating diseases associated with these biomarkers may have different drivers of autoimmunity.The rare coexistence of these 2 antibody biomarkers also points to distinct immunopathogeneses of these diseases. It has been postulated that MOG-IgG is an epiphenomenon, occurring with exposure of antigen in the AQP4-IgG disease. However, the rarity of dual positivity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 5 publications
3
16
2
Order By: Relevance
“…For instance, even in the absence of overt neurodegeneration, older adults show gradual changes in mental processes such as attention, memory retrieval, processing speed, and executive function (Harada et al, 2013;Schott, 2017). However, half of adults in the United States aged 50-64 years consider themselves at least somewhat at risk for developing overt dementia such as Alzheimer's disease (AD), and 37% report having a family member with dementia (Maust et al, 2020). These concerns encompass the wide range of AD symptoms-including progressive memory loss, agitation, language deficits, depression, mood disturbances, and even psychosis-and are not unfounded, as a growing percentage of the population does develop AD (Schott, 2017;Mehla et al, 2020).…”
Section: Introduction Alzheimer's Diseasementioning
confidence: 99%
“…For instance, even in the absence of overt neurodegeneration, older adults show gradual changes in mental processes such as attention, memory retrieval, processing speed, and executive function (Harada et al, 2013;Schott, 2017). However, half of adults in the United States aged 50-64 years consider themselves at least somewhat at risk for developing overt dementia such as Alzheimer's disease (AD), and 37% report having a family member with dementia (Maust et al, 2020). These concerns encompass the wide range of AD symptoms-including progressive memory loss, agitation, language deficits, depression, mood disturbances, and even psychosis-and are not unfounded, as a growing percentage of the population does develop AD (Schott, 2017;Mehla et al, 2020).…”
Section: Introduction Alzheimer's Diseasementioning
confidence: 99%
“…A recent systematic review indicated that nearly 50% of the general population, from various countries surveyed, viewed dementia as a normal part of aging and a non-preventable part of living ( 2 ). Similarly, in the Netherlands ( 3 ) and United States ( 4 ) individuals demonstrated difficulty in identifying risk factors related to dementia. Despite the general populations' beliefs, dementia is not a normal part of aging and certain factors have been linked to increasing dementia risk.…”
Section: Introductionmentioning
confidence: 99%
“…According to the current state of knowledge, dementia is an incurable progressive disease that ranks first among the age-related fears of people aged 60+ years [1], with close to 50% of all people aged 50+ being worried to develop the disease in the future [2]. The World Alzheimer Report [3] in 2016 estimated that currently around 50 million people are affected by dementia worldwide and that this number will double every 20 years [4] (the World Alzheimer Report is an annual publication with changing foci; its 2020 edition still refers to the cited report as the "most up-to-date global estimate").…”
Section: Introductionmentioning
confidence: 99%